(untitled) (Conference Zone, 2022)
This article is devoted to the study of the theoretical basis for testing and evaluation of hardness of materials and coatings of automotive parts in the measurement and testing laboratory "Uz Koram Co", the selection as a research object, as well as research methods and tools. consists of substantiation